Enhanced Aquatic Respiration Associated With Mixing of Clearwater Tributary and Turbid Amazon River Waters - Ward, Nicholas D.; Sawakuchi, Henrique O.; Richey, Jeffrey E.; Keil, Richard G.; Bianchi, Thomas S. (Frontiers in Earth Science, 2019)
When water bodies with unique biogeochemical constituents mix together there is potential for diverse responses by aquatic microbial communities and associated ecosystem functions. Here we evaluate bulk respiration under varying mixtures of turbid Amazon River water and two lowland tributaries—the Tapajós and Xingu rivers—based on O2 drawdown in dark rotating incubation chambers. Experiments containing 5%, 17%, 33%, and 50% tributary water mixed with Amazon River water were performed for the Tapajós and Xingu rivers at 3 different rotation velocities (0, 0.22, and 0.66 m s-1) during the falling water period. Pseudo first order reaction coefficients (k), a measure of respiration potential, ranged from -0.15 to -1.10 d-1, corresponding to respiration rates from 1.0 to 8.1 mg O2 L d-1. k values consistently increased with the rate of chamber rotation, and also was generally higher in the tributary-mainstem mixtures compared to pure endmembers. For both the Tapajós and Xingu rivers, the 17% mixture of tributary water yielded maximal k values, which were up to 2.9 and 2.2 times greater than in the tributary endmembers, respectively. The 50% mixtures, on the other hand, did not result in large increases in k. We hypothesize that enhanced respiration potential after mixing unique water is driven, in part, by microbial priming effects that have been previously identified on a molecular level for these rivers. The results of this study suggest that there may be an optimal mixture for priming effects to occur in terms of the relative abundance of “priming” and “primed” substrates.